(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
This article presents a synthetic and analytical accounting of financial result from the sale of products and the final financial result; reflects the operational and non-operating income and expenses from fines, penalties. And, also in this paper, we consider the differences, similarities and the interaction of tax and accounting. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 141-145